Total ozone variability and trends over the South Pole during the wintertime ... - Fioletov, Vitali; Zhao, Xiaoyi; Abboud, Ihab; Brohart, Michael; Ogyu, Akira; SIt, Reno; Lee, Sum Chi; Petropavlovskikh, Irina; Johnson, Bryan; Cullis, Patrick; Booth, John; McConville, Glen (GFZ German Research Centre for Geosciences, 2023)
<!--!introduction!--> The Antarctic polar vortex creates unique chemical and dynamic conditions when the stratospheric air over Antarctica is isolated from the rest of the stratosphere. As a result, stratospheric ozone within the vortex remains largely unchanged for a five-month period from April until late August when the sunrise and extremely cold temperatures create favorable conditions for rapid ozone loss. Such prolong stable conditions within the vortex make it possible to estimate the ozone levels there from sparse wintertime ozone observations at the South Pole. Total ozone measurements by Dobson and Brewer spectrophotometers that use the Moon as the light source, integrated ozonesonde profiles, and MERRA-2 reanalysis data were used to analyse ozone variability and trends over the South Pole. The wintertime ozone values over the South Pole during the last 20 years were 12%–15% below the pre-1980 level, i.e., the decline there was nearly twice larger than that over southern midlatitudes. It is ... : The 28th IUGG General Assembly (IUGG2023) (Berlin 2023) ...